A new method to predict values for postoperative lung function and surgical risk of lung resection by quantitative breath sound measurements - Westhoff, Michael; Dienemann, Hendrik (American journal of clinical oncology, 2013)
Objectives: We evaluated quantitative acoustic measurements, as a simpler alternative to perfusion scintigraphy, for estimation of predicted postoperative (ppo) lung function after resection surgery in our patient population. Methods: Patients with lung cancer, considered as candidates for lung resection, were enrolled in the study. All patients underwent lung function testing and quantitative breath sound testing by vibration response imaging (VRI) on the same day. A subset of patients also had perfusion testing. Forced expiratory volume in 1 second (FEV1) and diffusing capacity of the lung for carbon monoxide (DLCO) predictions derived from VRI testing were compared with perfusion values and actual FEV1 values at 1 month postoperatively. Results: Fifty-three subjects (40 males; age 66±8 y) participated. There was high correlation between both methods for the calculation of ppoFEV1% (R=0.94; n=39) and ppoFEV (L) (R=0.90; n=39). PpoFEV1 were 58±18% versus 56±20% and 1.69±0.49 L versus 1.62±0.52 L, based on perfusion and VRI methods, respectively. In 92% (36/39) of calculations, the difference between the 2 methods was <10%. High correlations also existed between VRI and perfusion for the calculation of ppoDLCO% (R=0.95; n=37) and ppoDLCO mL/min/mm Hg (R=0.90; n=37). VRI predictions showed good correlation for the 34 patients with actual postoperative lung function (R=0.88 and R=0.80 for FEV1% and FEV1L, respectively). Accuracy of the VRI to predict surgical risk (<40% cutoff threshold for ppo values) compared with actual postoperative values was 85% (29/34). Conclusions: Predictions of postoperative lung function using VRI agree well with radionuclide techniques and actual measured postoperative values. VRI may provide a noninvasive, simpler alternative for estimation of ppo values, particularly when perfusion testing is not readily available.
Gesehen am 16.04.2018